DEITIES AND DEMONS ON THE STREETS OF SEOUL: CONSTRUCTING SPACE IN THE SOUTH KOREAN FANTASY GENRE TV SERIES / БОЖЕСТВА И ДЕМОНЫ НА УЛИЦАХ СЕУЛА: КОНСТРУИРОВАНИЕ ПРОСТРАНСТВА В ЮЖНОКОРЕЙСКОМ ТЕЛЕСЕРИАЛЕ ЖАНРА «ФЭНТЕЗИ» - TARASOVA ALEKSANDRA V. / ТАРАСОВА А.В. (Наука телевидения)
This article attempts to identify the signs by which the fantasy genre is recognized. Whether in verbal texts or cinema, such generic signs, like signs of “the fantastic” in general, are difficult to be determined precisely. The subjects of this analysis are TV series and how they communicate with their audience. We consider the problem of generic signs in TV production in the context of historical and cultural features of the Republic of Korea. The present article focuses on two recent TV series, Dokkaebi and Hwayugi, both examples of so-called “urban fantasy”, set mainly in the capital, Seoul, in the present day. On the one hand, the audience for Korean fantasy would expect to see many original, vividly realized characters associated with the mythology of the region. On the other hand, the specificities of Korean religious culture, the influence of shamanism on everyday life (which is hard to be evaluated objectively), and the nature of some neo-Confucian customs complicate the traditional, albeit conditional, “western” oppositions of “natural” to “supernatural”, “ordinary” to “miraculous”. In search of “the fantastic” in the South Korean series, the article turns to the narration itself focusing on what combinations of visual and textual components allow the audience to recognize “the fantastic” and identify the characters in the series as inhuman beings, despite their contemporary costumes, and above all considers the transformations that the 21st century metropolis has to undergo in order to become a special habitat for deities and demons which at the same time can facilitate their interaction with human characters.